"You got to eat, but then what you are eating, it's going to kill you": Living with hypertension while experiencing homelessness. Issue 2 (6th September 2020) - Groton, Danielle B.; Leavitt, Mary A.; Opalinski, Andra S.
Abstract: Heart disease, including hypertension, is a leading cause of morbidity and mortality among persons experiencing homelessness (PEH). PEH exhibit a greater number of modifiable risk factors for hypertension than the general population and are challenged to reach optimal blood pressure control despite receiving medical treatment. This descriptive qualitative study used data collected from three focus groups to explore the barriers and facilitators of self‐management of hypertension while experiencing homelessness. Participants discussed co‐morbidity, limited food choices, medication issues, stress, and negative health care provider experiences as the biggest barriers toward self‐management of hypertension. To address the barriers described above, participants discussed strategies to manage their medications, healthy eating, exercise, social support, and reducing stress. Strategies for health care practitioners and shelter providers to reduce barriers to self‐management of hypertension among PEH are discussed.